2020
DOI: 10.1111/echo.14591
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Early Inflow‐Outflow Index—A new method for echocardiographic evaluation of right ventricle dysfunction in acute pulmonary embolism

Abstract: Introduction Acute pulmonary embolism (APE) is a cardiothoracic thromboembolic emergency at risk of life‐threatening. Several risk graduation algorithms may be applied to delineate short‐term mortality in patients with APE. In this study, we aim to depict the relationship between the right ventricular early inflow‐outflow (RVEIO) index, which is a Doppler‐based parameter, and the pulmonary embolism severity index(PESI) in acute pulmonary embolism. Methods In the presented study, a total of 160 patients who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Recently, the RV early inflow-outflow (RVEIO) index has been identified as a possible and indirect marker of the severity of tricuspid regurgitation and RV dysfunction in pulmonary embolism. 8,9 Previous studies have emphasized that ultrasonographic examinations, especially lung ultrasound (LUS), can provide information about the lung involvement and the severity of pneumonia in COVID-19 patients. 10,11 However, no study was found in the literature investigating the relationship between echocardiographic parameters and the severity of pneumonia.…”
mentioning
confidence: 99%
“…Recently, the RV early inflow-outflow (RVEIO) index has been identified as a possible and indirect marker of the severity of tricuspid regurgitation and RV dysfunction in pulmonary embolism. 8,9 Previous studies have emphasized that ultrasonographic examinations, especially lung ultrasound (LUS), can provide information about the lung involvement and the severity of pneumonia in COVID-19 patients. 10,11 However, no study was found in the literature investigating the relationship between echocardiographic parameters and the severity of pneumonia.…”
mentioning
confidence: 99%
“…In COVID-19, 11,12 RV abnormalities can be noted in 66%, and moderate or severe TR in 21% of patients, 11 both of which could elevate RVEIO, the former being related to COVID-19 mortality. 12 The current study is one of only three early RVEIO studies, [2][3][4] one of which actually showed no association between RVEIO and mortality in COVID-19. 4 To understand this discrepancy, we must first realize the preliminary nature of this area of study.…”
mentioning
confidence: 78%
“…We found the article by Kahyaoglu M et al 1 on the right ventricular early inflow-outflow (RVEIO) index intriguing, but accompanied by only a meager amount of other publications on this topic. [2][3][4] The study evaluated the RVEIO index with COVID-19 pneumonia severity, and we, like Oliver, are left wanting more.…”
mentioning
confidence: 99%
See 2 more Smart Citations